(untitled) (Hekima Review, 2020)
This article argues that the development of theological discourse will depend on robust, sustainable publishing models nurtured within Africa. Such models not only take into account inherent challenges for scholarly writing on the continent, they also forge ahead to harness technology to generate content that is both accessible and affordable. The article highlights publishers such as Orbis whose work profoundly improved the publishing landscape in the last three decades. The article then presents African Theological Network (ATNP) as a collaborative model that holds promise for the future of publishing in Africa.